Cross Country Evidence on Consumption Persistence - Belbute, José (2014)
The main focus of this article is the detection and measurement of the level of persistence in aggregate and disaggregate private consumption in Italy, Norway and the United Kingdom. Using a non-parametric methodology, we conclude that the presence of a significant degree of persistence in aggregate and disaggregate consumption in those three countries cannot be rejected. These results are essential from a policy point of view. Persistence in consumption does exist and cannot be ignored, whether the goal is to stabilize the level of output via consumption or to boost output via long-lasting increases in consumption. One instrument that might be useful in addressing this issue is interest rates.